Auditoría de gestión y su incidencia en el departamento de talento humano del gobierno autónomo descentralizado municipal del cantón “Mocache”, año 2014. - Ramírez Bueno, Virginia Leticia (2016)
This research project was developed in the Decentralized Autonomous Municipal Government of the canton "Mocache", in order to audit management in the Human Resource department. In addressing the methodological strategies for obtaining effective and efficient information on the conduct of the audit were implemented, which aims to raise awareness of the reality on the management that is carried in the Department where they could find the weaknesses and strengths through the application of indicators and evaluation of internal control system. From the results obtained during Auditing confidence level of 57.00% (MODERATE HIGH) was obtained, determining that the Municipal institution audits are conducted irregularly, while the level of control risk 43 , 00% (MODERATE LOW), 35.00% inherent risk and detection risk assumed one 15.00%, resulting in a 2.25% of audit risk. We performed the analysis of the strategic map and management indicators took a 22.86% reflecting failure in certain activities, also could be determined which has an effectiveness level of 80% for achieving the defined objectives, there is a low level staff training, so it is recommended to improve compliance with the regulations and standards set out in COOTAD public servants, to optimize the structural and functional work, as the highest authority consider the importance of training to Talent human, the same that allow you to make a proper assessment of the management and performance of different institutional activities carried out in the Municipal Bank.